Preparation, in vitro screening and molecular modelling of symmetrical bis-quinolinium cholinesterase inhibitors--implications for early myasthenia gravis treatment - Komloova, Marketa; Musilek, Kamil; Horova, Anna; Holas, Ondrej; Dohnal, Vlastimil; Gunn-Moore, Frank; Kuca, Kamil (Bioorganic & medicinal chemistry letters, 2011)
This paper describes the preparation and in vitro evaluation of 18 newly prepared bis-quinolinium inhibitors on human recombinant acetylcholinesterase (AChE) and human plasmatic butyrylcholinesterase (BChE). Their inhibitory (IC(50)) and was compared to the chosen standards ambenonium dichloride, edrophonium chloride, BW284c51 and ethopropazine hydrochloride. One novel compound was found to be a promising inhibitor of hAChE (in nM range) and was better than edrophonium chloride or BW284c51, but was worse than ambenonium chloride. This compound also showed selectivity towards hAChE and it was confirmed as a non-competitive inhibitor of hAChE by kinetic analysis. A molecular modelling study further confirmed its binding to the peripheral active site of hAChE via apparent π-π or π-cationic interactions.
Keywords: Butyrylcholinesterase; Molecular Dynamics Simulation; butyrylcholinesterasa; Acetylcholinesterase; Kinetics; Quinolinium Compounds; edrofonium; vazebná místa; myasthenia gravis; vazba proteinů; Structure-Activity Relationship; lidé; rekombinantní proteiny; Recombinant Proteins; simulace molekulární dynamiky; benzenaminium, 4,4'-(3-oxo-1,5-pentandiyl)bis(N,N-dimethyl-N-2-propenyl-), dibromid; Myasthenia Gravis; chinolinové sloučeniny; acetylcholinesterasa; Edrophonium; ambenoniumchlorid; Ambenonium Chloride; vztahy mezi strukturou a aktivitou; Benzenaminium, 4,4'-(3-oxo-1,5-pentanediyl)bis(N,N-dimethyl-N-2-propenyl-), Dibromide; cholinesterasové inhibitory; Cholinesterase Inhibitors; Protein Binding; kinetika; Binding Sites; Humans